Understanding the Rotational Positioning of the Bones in the Medial Column of the Foot: A Weightbearing CT Analysis. Issue 4 (22nd October 2020) - Silva, Thiago A.; Baumfeld, Daniel; Li, Shuyuan; Mansur, Nacime S.; Lintz, Francois; Nery, Caio A.; Godoy-Santos, Alexandre L.; Wagner, Pablo; Wagner, Emilio; Dibbern, Kevin N.; Femino, John E.; de Cesar Netto, Cesar
Category: Bunion; Midfoot/Forefoot Introduction/Purpose: Rotational deformities of the first ray have been described as essential components of hallux valgus (HV) deformity, influencing its severity and progression. The exact deformity location along the medial column, as well as the typical rotational pattern of each bone, is yet to be fully understood. The objective of this study was to evaluate the rotational position of the navicular, medial cuneiform, first metatarsal and proximal phalanx using three-dimensional weightbearing CT (WBCT) images of a diversity of patients with foot pathologies. Our goal was to describe the rotational profile of medial column bones, serving as a reference for future studies. Methods: A retrospective review of patients that underwent WBCT assessment of multiple foot and ankle pathologies was conducted in a single Institution. A blinded and independent Fellowship-Trained Foot and Ankle Orthopedic Surgeon performed measurements in Multiplanar Reconstruction (MPR) WBCT images assessing the rotational profile of each bone of the medial column (navicular, medial cuneiform, first metatarsal and proximal phalanx of the great toe), as demonstrated in the attached figure. The first metatarsal, representing a long bone, was evaluated on its proximal and distal ends. A total of 110 patients were included. As standard, we considered pronation as positive values and supination as negative values. Comparisons were performed using independent t-tests or Wilcoxon tests. P-values of <0.05 were considered significant. Results: The mean values and 95% Confidence Interval for the rotational profile of the medial column bones were found to be respectively: Navicular, pronated 43.2o (41.1 to 45.2); Medial Cuneiform, supinated -2.5o (-4.3 to -0.7); Proximal First Metatarsal, supinated -28.1o (-32 to -24.1); Distal Metatarsal, pronated 18.5o (16.3 to 20.7); First Toe Proximal Phalanx, pronated of 21.6o (18.7 to 24.5). Significant differences were found in the rotational position of each bone/segment (p<0.0001), with the exception of the distal metatarsal/proximal phalanx (p=0.11), that demonstrated similar amounts of pronation. When considering each segment/joint in isolation, the highest rotational deformity was found to exist within the first metatarsal (pronated 46.6o), naviculo-cuneiform joint (supinated 45.7o), first tarsometatarsal joint (supinated 25.5o) and first metatarsophalangeal joint (pronated 3.1 o). Conclusion: Our study described the rotational profile of the medial column bones using WBCT images, in a population of patients with diverse foot and ankle pathologies. We found significant differences in the rotational position of most of the bones along the medial column. The greatest amount of rotation was found to happen within the first metatarsal, which undergoes an average of 46o of pronation from proximal to distal, probably compensating a considerable amount of supination of the naviculo- cuneiform and first tarsometatarsal joints. Further studies comparing hallux valgus patients and controls are needed.